2003
DOI: 10.14411/eje.2003.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on development and reproduction in Gastrophysa viridula (Coleoptera: Chrysomelidae)

Abstract: Abstract. The duration of development, reproduction and longevity of Gastrophysa viridula (DeGeer) was measured at constant temperatures and a long day photoperiod. At 18, 21.5, 25, and 28°C the average duration of development ofthe egg, larval and pupal stages and total development time (28.2, 21.6, 16.1, 15.0 days) decreased with temperature hut the proportion of time spent in the egg, larval and pupal stages did not significantly change with temperature. Total development required 304.6 day degrees ahove th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…Temperature determines the duration of development (Honek et al 2003) (Table 2). At constant 18°C the mean pre-adult development time is c. 28 days, at 28°C its duration decreases to 15 days.…”
Section: Life Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature determines the duration of development (Honek et al 2003) (Table 2). At constant 18°C the mean pre-adult development time is c. 28 days, at 28°C its duration decreases to 15 days.…”
Section: Life Historymentioning
confidence: 99%
“…Thermal constants (Table 3), lower development threshold 7.1°C and sum of effective temperatures for total development 304.6 day-degrees were calculated. Statistical analysis revealed that the lower development threshold was common for all development stages: egg, larva and pupa (Honek et al 2003). The existence of an identical development threshold for all development stages is called rate isomorphy (Jarosik et al 2002) and is of great practical importance because it greatly facilitates calculating the thermal constants.…”
Section: Life Historymentioning
confidence: 99%
“…Since the rate isomorphy is a consequence of equality among the lower developmental thresholds, statistical methods (Jarosik et al 2002(Jarosik et al , 2004Honek et al 2003;Shi et al 2010) were used for comparing the lower development thresholds. In this method, ratios of time spent in each developmental stage (proportion) at different constant temperatures were calculated from the data on the duration of development in a particular stage divided by the total pre-imaginal development (egg + larva + pupa).…”
Section: Rate Isomorphymentioning
confidence: 99%
“…This drop could be caused by higher temperature during the year 2006. According to Honěk (2003), McAvoy and Kok (2004), the temperature influenced occurrence and development of the pests in crops.…”
Section: Spring Barleymentioning
confidence: 99%